Continuing medical education program completion and influencing factors: a cross-sectional study in Sichuan Province, China - Liu, Xuedong; Ye, Mengliang (Frontiers in Medicine, 2024)
Objectives: This cross-sectional study was designed to explore the completion of continuing medical education (CME) programs and identify the factors influencing their completion.The data for this study were generated from the National CME Program Application and Information Feedback Online System and the Sichuan CME Administrative Platform. The data were processed using descriptive analysis, Chi-square test, and binary logistic regression methods. The completion of each CME program was determined by the research team members according to the criteria created by the Office of the Sichuan CME Commission.Results: A total of 180 hospitals and 3622 CME programs were included. Among the 3622 CME programs, 2936 (81.1%) were determined to be completed. Comparative analysis showed that in terms of hospital characteristics, specialist hospitals, county hospitals, hospitals with 500-1000 beds, and hospitals in the regions with government medical expenditure input equal to or more than 3000 million RMB displayed the highest completion rates. For program attributes, national programs, programs in the field of pharmacy, and programs with 1-3 duration days demonstrated the highest completion rates. The binary logistic regression analysis showed that hospital region with different government medical expenditure input had the strongest positive association with the completion of CME programs [OR=2. 922,], while the duration time showed the strongest negative association [OR=0.235, 95%CI (0.141-0.393)]. Conclusion: This is the first study in China to analyze the completion of CME programs and identify its influencing factors at the provincial level. It is recommended that the government in the region should pay great attention to the construction of measures regarding the factors affecting the